Governing Professionals Through Discourses of Resilience and Value: A New Legitimation for Ontario Pharmacists - Timothy Mickleborough; Linda Muzzin; Maria Athina Martimianakis (Professions and Professionalism, 2023)
In a neoliberal turn, the government of Ontario cut more than $750 million in funds that were traditionally received by pharmacies through dispensing medication. These funds were replaced with a state-funded program that would reimburse pharmacists for professional services related to patient care. The problem facing professional elites from Ontario pharmacy’s advocacy body was how to govern members of a self-regulating profession to switch subjectivities (identities) from the traditional dispenser of medication to providing patient care for profit. We address a gap in the literature and pose the question, how are the rank and file of allied healthcare professions governed by professional elites to become responsibilized subjects who will adopt state/profession agendas? Using a Foucauldian governmentality framework, our findings reveal that the rank and file are governed by elites through two technologies: resilience and value making possible a new “legitimate” pharmacist subjectivity related to the market and health care sustainability.